Anti-CCR4 monoclonal antibody enhances antitumor immunity by modulating tumor-infiltrating Tregs in an ovarian cancer xenograft humanized mouse model. (3rd March 2016) - Chang, De-Kuan; Peterson, Eric; Sun, Jiusong; Goudie, Calum; Drapkin, Ronny I.; Liu, Joyce F.; Matulonis, Ursula; Zhu, Quan; Marasco, Wayne A.
ABSTRACT: Recent studies have demonstrated that regulatory T cells (Tregs) are recruited to tumor sites where they can suppress antitumor immunity. The chemokine receptor CCR4 is expressed at high levels on functional CD4 + CD25 + FoxP3 + Tregs and production of the CCR4 ligand CCL22 by tumor cells and tumor-associated macrophages is associated with Treg recruitment to the tumor site. Here, we tested IgG1 and IgG4 isotypes of human anti-CCR4 mAb2-3 for their in vitro activity and in vivo capacity in a NSG mouse model bearing CCL22-secreting ovarian cancer (OvCA) xenograft to modulate Tregs and restore antitumor activity. Both mAb2-3 isotypes blocked in vitro chemoattraction of Tregs to CCL22-secreting OvCA cells. However, they differed in their in vivo mode of action with IgG1 causing Treg depletion and IgG4 blocking migration to the tumors. Primary T cells that were primed with OvCA-pulsed dendritic cells (DCs) demonstrated INFγ secretion that could be enhanced through Treg depletion by mAb2-3. Humanized mice reconstructed with allogeneic tumor-primed T cells (TP-T) were used to evaluate the restoration of OvCA immunity by depletion or blockade of Tregs with mAb2-3. We observed that IgG1 was more potent than IgG4 in inhibiting tumor growth. Mechanism studies demonstrated that mAb2-3 treatment lead to inhibition of IL-2 binding to its receptor. Further studies showed that mAb2-3 induced CD25 shedding (sCD25) from Tregs which lead to a decrease in IL-2-dependent survival. Together, the results demonstrate that mAb2-3 is an agonist antibody that can restore anti-OvCA immunity through modulation of Treg activity.